2021
DOI: 10.3389/fcell.2021.728352
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Sox2+ Glial Cells Are Potent Progenitors for Spiral Ganglion Neuron Reprogramming Induced by Small Molecules

Abstract: In the mammalian cochlea, spiral ganglion neurons (SGNs) relay the acoustic information to the central auditory circuits. Degeneration of SGNs is a major cause of sensorineural hearing loss and severely affects the effectiveness of cochlear implant therapy. Cochlear glial cells are able to form spheres and differentiate into neurons in vitro. However, the identity of these progenitor cells is elusive, and it is unclear how to differentiate these cells toward functional SGNs. In this study, we found that Sox2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…For instance, glial cells expressing PLP1 and SOX2 can be efficiently converted into new auditory neurons following overexpression of genetic factors, including the transcription factors Ascl1 and NeuroD1 [ 39 ], Neurog1 and NeuroD1 [ 37 ] and the RNA binding protein lin-28 [ 38 ]. Such a conversion of spiral ganglion glial cells to auditory neurons has also been demonstrated following pharmacological reprogramming [ 40 ]. However, a direct conversion (i.e., trans-differentiation) is also possible, thereby, raising the problem of an exhaustion of the supporting cell pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, glial cells expressing PLP1 and SOX2 can be efficiently converted into new auditory neurons following overexpression of genetic factors, including the transcription factors Ascl1 and NeuroD1 [ 39 ], Neurog1 and NeuroD1 [ 37 ] and the RNA binding protein lin-28 [ 38 ]. Such a conversion of spiral ganglion glial cells to auditory neurons has also been demonstrated following pharmacological reprogramming [ 40 ]. However, a direct conversion (i.e., trans-differentiation) is also possible, thereby, raising the problem of an exhaustion of the supporting cell pool.…”
Section: Discussionmentioning
confidence: 99%
“…The WNT agonist CHIR99021, in combination with other pharmacological treatments, has also been shown to promote the conversion of SOX2 expressing glial cells to auditory neurons [ 40 ]; however, its potential to promote ANPG expansion has been poorly studied. In our hands, stimulating the WNT pathway was able to enhance ANPGs growth, however, not to a level sufficient to achieve significant passaging and amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome profiling of cells at different stages of SGNs differentiation, including exogenous stem cell-derived and endogenous glial cell-derived SGNs regeneration, could provide useful information about the molecular processes involved. Most recently, the emerging cell transcriptome analysis such as single-cell RNA sequencing and bulk RNA-sequencing have been applied in identifying the subtypes of SGNs and inner ear glial cells, characterizing the dynamic expression pattern of SGN genes, and analyzing the transcriptome of the induced neurons after regeneration (Shrestha et al, 2018 ; Sun et al, 2018 ; Li C. et al, 2020 ; Chen et al, 2021 ; Tasdemir-Yilmaz et al, 2021 ). For example, Li C. et al ( 2020 ) compared the transcriptomes of SGNs and two other inner ear cell types, HCs and glia to identify genes that were expressed specifically in SGNs within the cochlea and exhibited either constant (e.g., Scrt2) or dynamic (e.g., Celf4) expression patterns.…”
Section: Transcriptome Analysis and Sgns Regenerationmentioning
confidence: 99%
“…These genes might represent promising candidate regulators of SGN cell-fate determination and/or differentiation. Chen et al ( 2021 ) performed transcriptomic analysis of the glial cells-derived SGNs under different stimuli conditions in vitro and found that the small molecules cocktail FIBCL treatment promoted the newborn SGNs maturation. Despite the transcriptome analysis of the inner ear cells still facing some challenges such as a limited number of cells obtained from the cochleae, the lower cell viability, etc.…”
Section: Transcriptome Analysis and Sgns Regenerationmentioning
confidence: 99%
“…The passive K + conductance channels, which give rise to very low membrane resistance and linear current–voltage (I–V) relationship, are unique features that define mature astrocytes in the brain (Bae et al, 2020; Mi Hwang et al, 2014; Zhou et al, 2021). GLSs also participate in the maturation, proliferation, protection, and regeneration of cochlear cells (Chen, Huang, et al, 2021; Ramírez‐Camacho et al, 2006) like glial cells in the brain. When hair cells are damaged, they are extruded from the epithelium, phagocytosed by surrounding GLSs and nearby GLSs fill in the gap, leaving a cross‐shaped F‐actin scar (Bird et al, 2010; Raphael & Altschuler, 1991; Wagner & Shin, 2019).…”
Section: Introductionmentioning
confidence: 99%